Population composition and seasonal dynamics of mosquito communities across landscape gradients in southern Africa, with emphasis on selected arbovirus vector species and their role in disease transmission - Braack, Lawrence Edward Oliver (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2020.